The Criminal Legal Framework for Classifying ISIS's Actions in Iraq as Genocide - Ragab, Rania (Journal of Legal Sciences, 2026)
Genocide is one of the most serious crimes against humanity, targeting the destruction of human groups based on national, ethnic, or religious identity. ISIS committed horrific crimes against religious minorities in Iraq, including the Yazidis and Christians, encompassing mass killing, forced displacement, sexual enslavement, and destruction of religious sites. This research examines the international legal framework for genocide under the 1948 Convention and the 1998 Rome Statute, analyzes the applicability of its legal elements to ISIS's conduct in Iraq, and identifies the criminal responsibility of perpetrators and the available international mechanisms for achieving justice.